2003
DOI: 10.1038/nature01335
|View full text |Cite
|
Sign up to set email alerts
|

Ankyrin-B mutation causes type 4 long-QT cardiac arrhythmia and sudden cardiac death

Abstract: Mutations in ion channels involved in the generation and termination of action potentials constitute a family of molecular defects that underlie fatal cardiac arrhythmias in inherited long-QT syndrome. We report here that a loss-of-function (E1425G) mutation in ankyrin-B (also known as ankyrin 2), a member of a family of versatile membrane adapters, causes dominantly inherited type 4 long-QT cardiac arrhythmia in humans. Mice heterozygous for a null mutation in ankyrin-B are haploinsufficient and display arrhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
876
1
23

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 877 publications
(941 citation statements)
references
References 18 publications
41
876
1
23
Order By: Relevance
“…To date, however, high resolution electron micrographs have not specifically revealed such an organization -nor have they denied it. Nevertheless, RyR2s are organized tightly with LTCCs as shown by the Moore group [26], a requirement for local control of EC coupling [27][28][29], while our group and others have demonstrated that IP 3 Rs, ankyrin-B, Na + /K + ATPase, Na + /Ca 2+ exchanger and Na + channels (Na v 1.5) are co-localized nearby at the Z-line [16,17,30,31]. These findings suggest a spatial organization shown in Fig.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…To date, however, high resolution electron micrographs have not specifically revealed such an organization -nor have they denied it. Nevertheless, RyR2s are organized tightly with LTCCs as shown by the Moore group [26], a requirement for local control of EC coupling [27][28][29], while our group and others have demonstrated that IP 3 Rs, ankyrin-B, Na + /K + ATPase, Na + /Ca 2+ exchanger and Na + channels (Na v 1.5) are co-localized nearby at the Z-line [16,17,30,31]. These findings suggest a spatial organization shown in Fig.…”
supporting
confidence: 57%
“…The subcellular localization of IP 3 Rs in cardiac myocytes has received increasing attention as the field attempts to define the function of these channels. In ventricular myocytes, immunofluorescence studies show that IP 3 Rs are found at the Z-lines, in the perinuclear region and in the nuclear membrane [7,16,17]. Moreover, IP 3 Rs are found in similar locations in both atrial [12] and Purkinje myocytes [18][19][20]).…”
mentioning
confidence: 99%
“…Consistent with this notion, IP 3 Rs have been localized close to the dyadic junctions where excitation-contraction coupling is initiated [142], and direct activation of IP 3 Rs was found to enhance Ca 2+ spark occurrence throughout ventricular cells [41]. Furthermore, application of hormones that activate the production of IP 3 inside ventricular myocytes, such as endothelin-1 [11], enhances systolic Ca 2+ signals in rat and rabbit cells [41,128,143].…”
Section: Ip 3 Signaling In Ventricular Myocytesmentioning
confidence: 62%
“…High affinity interaction between ankyrin-B and IP 3 R is required for posttranslational stability and targeting of the IP 3 R to SR microdomains closely opposed to neighboring T tubules [178,179]. Loss-of-function mutations in ankyrin-B cause reduction of IP 3 Rs in specialized SR-T tubule junctions (distinct from the classical dyads) in cardiac myocytes and are associated with arrhythmias ranging from bradycardia, sinus arrhythmia, atrial fibrillation and catecholaminergic polymorphic ventricular tachycardia to ventricular fibrillation both in humans and in mice heterozygous for a null mutation in ankyrin-B (ankyrin-B +/− mice) [142,180]. In patients affected by ankyrin-B mutations, emotional or physical stress may lead to syncopes and sudden death.…”
Section: Arrhythmias Related To Ankyrin-b Mutationsmentioning
confidence: 99%
See 1 more Smart Citation